Preparation and in vitro evaluation of synthetic high-density lipoproteins as parenteral drug delivery system for tamoxifen citrate - Radhi, Ameerah; Ali, Wedad K.; Al-Saedi, Fitua (Iraqi Journal of Pharmaceutical Sciences, 2023)
The aim of this study was to develop a bioinspired drug delivery system for tamoxifen citrate (TC) based on synthetic high density lipoproteins (sHDL). For this purpose, sHDL nanoparticles were prepared from a mimetic peptide (5A peptide) and different lipids using thin film hydration method followed by sonication and thermal cycling. Various formulation parameters including lipid composition, lipid to peptide ratio, and drug to carrier ratio had a remarkable impact on the properties and the release pattern of the nanoparticles. The optimized formula (F14) displayed a spherical morphology, average diameter of (35.7±12.4) nm, and a zeta potential (ζ) equals to (-48.4± 0.5) mV. The encapsulation efficiency and drug loading of F14 were (96.5±0.7%) and (9.65±0.1%), respectively. Besides, F14 showed a good stability in human plasma for 24 hours. The encapsulation of the lipophilic drug within the hydrophobic core of the nanocarrier enabled a slow drug release from nanoparticles which follows a near zero order controlled mechanism. The promising results of this study opens an avenue for using sHDL as a delivery system for administration of TC intravenously. Therefore, the optimized formula is suggested to be subject for future analyses in terms of in vitro cytotoxicity against breast cancer cells and in vivo evaluation in tumor bearing animals.